EFFECTIVE SEISMIC TECHNOLOGIES FOR NEW GEOLOGICAL DISCOVERIES IN EAST SIBERIA - A. V. Gaiduk; D. N. Tverdokhlebov; E. A. Danko; E. I. Dolgova; A. B. Kleshnin; V. A. Grinchenko; E. I. Goguzeva; A. S. Chirgun (Геодинамика и тектонофизика, 2021)
Currently, East Siberia as a whole and the Republic of Sakha (Yakutia) in particular are the territories of extensive geological exploration. Field geophysical surveys are mainly performed by seismic technologies used to discover new deposits and provide data for detailed appraisal of the known fields. Three-dimensional seismic surveys are effectively used for clarifying the details of geologic structures and obtaining the data for drilling programs. Upon further development of technologies, improvements are introduced in field operations, seismic data processing and interpretation, and drilling programs. As the information content of the survey data increases, it becomes possible to revise and update geological models and/or develop them in a more detail. With the use of modern data processing technologies that preserve the signals and depth migration data, the tectonic model of the Srednebotuobinskoe Oil and Gas Condensate Field was fully modified. Furthermore, additional isolated tectonic blocks were discovered in the eastern part of the Central deposit, and their map was constructed. The geological exploration based on the updated tectonic model is successful – new mineral reserves have been discovered, and the vector of geological exploration has been completely changed.